Assessing vegetable farming practices in a floodplain village of Kamrup District, Assam, India - Bhattarai, Saraswati; Bhagabati, Abani Kumar Bhagabati (Asian Journal of Agriculture and Rural Development, 2025)
Farming practices in a floodplain environment hold immense ecological, economic, and social significance. The current study focuses on Choutara village, located in Kamrup District, Assam. The primary objective of the research is to evaluate the adaptive techniques employed by local vegetable farmers in response to recurring environmental stresses, including seasonal flooding, waterlogging, and soil erosion. The research aims to understand the long-term effects of these stressors on crop selection, land use decisions, and agricultural productivity. The study used a mixed-methods approach, integrating qualitative and quantitative methodologies. Primary data were collected via field surveys, oral interviews with aged farmers, and focused group discussions. Supplementary secondary data were examined to comprehend past trends. Descriptive statistics and comparative analysis were employed to investigate production patterns and discern changes in agricultural practices over different seasons and flood cycles. The findings indicate a dynamic adaptation process among farming households, which integrates indigenous agricultural knowledge with specific modern practices to address climate risks and market variation. Agriculturalists have diversified their planting schedules, chosen short-duration and flood-resistant vegetable cultivars, and adapted soil and water conservation techniques. The study highlights the need to enhance institutional assistance, encompassing infrastructural development, the availability of timely meteorological data, and agricultural extension services tailored to the specific requirements of floodplains. Policy-makers and development organizations can utilize these insights to formulate more adaptive and contextually relevant initiatives to improve the sustainability and productivity of floodplain agriculture.